Simulation study on speed control of permanent magnet direct-driven system for mining scraper conveyor. (2018) - Lu, En; Li, Wei; Yang, Xuefeng; Xu, Shaoyi
A simulation method of speed control based on the load characteristic of the permanent magnet direct-driven system is presented for mining scraper conveyor. Firstly, the mathematical model of permanent magnet synchronous motor (PMSM) is established based on the coordinate transformation theory. Subsequently, the closed loop speed controller of permanent magnet direct-driven systems is designed on the basis of sliding mode control theory and motor model. The chain characteristics of scraper conveyor are described by Kelvin-Vogit model, and the dynamic model of the overall scraper conveyor system is established with distinct element method. Then, according to the coupling relationship between the permanent magnet direct-driven system and the scraper conveyor, the simulation model of the scraper conveyor is established by using MATLAB/Simulink module. The simulation results demonstrate that the permanent magnet direct-driven system can realise smooth starting of the scraper conveyor, and the random load and polygonal sprocket wheel can influence the stability of speed control system.